Pragmatism over Piety: Understanding Muslim Electoral Choices in East Nusa Tenggara’s Local Elections - Gai, Apolonaris; Kushandajani, Kushandajani; Alfirdaus, Laila Kholid; Herawati, Nunik Retno (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
This article explores the electoral behaviour of Muslim voters in the 2024 Gubernatorial Election of East Nusa Tenggara (NTT), Indonesia. Motivated by concerns over the political marginalisation of Muslim candidates in NTT’s local elections and the wider discourse on minority political participation, the study adopts a voting behaviour framework that integrates sociological, psychological, and rational-choice approaches. It examines how sociocultural backgrounds, religious identity, economic considerations, and political affiliations influence Muslim voting preferences. The analysis also considers the role of historical voting patterns, political party dynamics, and the influence of prominent Islamic figures and organisations. Set in a Christian-majority province, the study investigates the interplay between identity politics, economic rationality, and political pragmatism. Findings suggest that Muslim voters exhibit a nuanced approach to leadership selection, prioritising democratic values, visionary governance, and service-oriented leadership over narrow religious affiliations. Interview data reveal that qualities such as empathy, populism, decisiveness, and moral integrity—particularly a strong anti-corruption stance—are highly valued. Voters also emphasise the importance of political and administrative experience, while viewing intelligence, religiosity, and military credentials as supplementary advantages. Overall, Muslim voters in NTT seek leaders who combine intellectual competence with emotional proximity to the electorate and a deep commitment to public welfare. This research contributes to the broader understanding of minority political agency in Indonesia and highlights the need for more inclusive political frameworks to promote equitable representation and strengthen democratic practices in multi-religious societies.